2012
DOI: 10.2737/nrs-gtr-98
|View full text |Cite
|
Sign up to set email alerts
|

Silvicultural guide for northern white-cedar (eastern white cedar)

Abstract: Northern white-cedar (eastern white cedar; Thuja occidentalis L.) is an important tree species in the northeastern United States and adjacent Canada, occurring both in pure stands and as a minor species in mixed stands of hardwoods or other softwoods. Yet practitioners have little and often contradictory information about cedar ecology and silviculture. In response to this information need, a group of university and government researchers in the United States and Canada embarked on more than a decade of collab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 53 publications
2
40
0
Order By: Relevance
“…In fact, our model predicted that diameter growth could respond over a range of sizes. A similar growth increase with DBH up to 50 cm has also been reported from a large data set of permanent plots distributed across eastern Canada and northeastern USA [1]. In their study, Hofmeyer et al [19] also found that even the oldest trees had relatively constant radial increment, which meant increased basal area increment.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In fact, our model predicted that diameter growth could respond over a range of sizes. A similar growth increase with DBH up to 50 cm has also been reported from a large data set of permanent plots distributed across eastern Canada and northeastern USA [1]. In their study, Hofmeyer et al [19] also found that even the oldest trees had relatively constant radial increment, which meant increased basal area increment.…”
Section: Discussionsupporting
confidence: 56%
“…Instead, we could interpret this overall tendency as progressive access better canopy positions through time. This capacity to maintain consistent growth at large sizes is consistent with the high longevity of the species [1].…”
Section: Discussionsupporting
confidence: 53%
“…In addition, the PL and PEF sites, which were both subject to heavy browsing, had very similar height class distribution patterns, regardless of differences in climate, stand composition, and partial cutting regime. Browsing has already been suggested as a predominant factor to explain the low recruitment of northern white-cedar seedlings to larger size classes, but its impact can be very variable, depending on local herbivore densities [1,3,26,28]. Deer are the most important predators of northern white-cedar seedlings and saplings, especially in winter, and may cause mortality by recurrent browsing [29].…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the greater vulnerability to deer browsing of 30 to 130 cm seedlings, compared to smaller seedlings and taller saplings [27]. Northern white-cedar is mostly a winter food, thus the snow cover generally protects the smallest seedlings, while the foliage of saplings >130cm is more difficult to reach, even considering that deer can browse to heights of up to 200 cm [1,3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation